Adverse events of surgical extrusion in treatment for crown–root and cervical root fractures: a systematic review of case series/reports. Issue 1 (25th June 2013) - Elkhadem, Ahmed; Mickan, Sharon; Richards, Derek
Abstract Background Crown–root and cervical root fractures constitute a restorative challenge due to sub‐gingival position of the fracture margin. Surgical tooth extrusion is one of the treatment options. There is uncertainty regarding the prognosis of such treatment modality. Objective To assess adverse events of surgical tooth extrusion in the treatment for crown–root and cervical root fractures in permanent teeth. Methods PubMed, Embase, and Google Scholar were searched through 15th of June 2012. Search was limited to English and Arabic languages. Reference list of relevant studies were hand‐searched. Grey literature was searched using Open Grey. Two review authors independently extracted data, while only one assessed trial quality using 8‐point methodological index for non‐randomized studies (MINORS) scale. A sensitivity analysis was performed to exclude studies with suspected patients' duplicates. Results Eleven case reports and eight case series involving 226 patients with 243 teeth were identified. No randomized controlled trials were found. The mean quality score for all case series was 9 suggesting a fair quality, while that of all case reports was 5 suggesting poor quality. Non‐progressive root resorption is the most common finding following surgical extrusion with an event rate of 30% (95% CI 24.6–36.7%). This is followed by low event rates of tooth loss (5%), slight mobility (4.6%), marginal bone loss (3.7%), and progressive root resorption (3.3%). No ankylosis occurred to any extruded tooth, while severe tooth mobility showed negligible overall event rate of 0.4%. Conclusion The available evidence suggests that surgical tooth extrusion is a valid technique in management of crown–root and cervical root fracture of permanent teeth. Minimal adverse events and good prognosis are expected. Further, surgical extrusion can be considered as a treatment option in teeth suffering sub‐gingival decay.